Mississippi blood : a novel - Iles, Greg (William Morrow, an imprint of HarperCollins Publishers, 2017)
"The exhilarating, highly anticipated final volume in the epic trilogy featuring Penn Cage from #1 New York Times bestselling author Greg Iles"--